Dead and Dying Shopping Malls, Re‐Inhabited. (6th September 2017) - Dunham‐Jones, Ellen; Williamson, June
Abstract : The living dead could be coming to a shopping centre near you! Zombie paintball experiences are just one of many inventive reuses of failing malls identified by architectural educators and writers Ellen Dunham‐Jones and June Williamson, who have been tracking trends in suburban retrofits for over a decade. From medical facilities to megachurches, and from offices to community colleges, they cite projects the length and breadth of the US – and beyond – that take advantage of the vast floor areas and parking facilities of these sites, and give them a sustainable future.